A simulation model and experimental study of X-ray transmission through a polycapillary focusing X-ray lens. Issue 1 (February 2020) - Wang, X Y; Luo, H; Zhou, M; Duan, J Y; Li, Y D; Lin, X Y
Abstract: A simulation model is established to simulate the X-ray transmission performance through a polycapillary focusing X-ray lens whose configuration curve was described by a piecewise function. The shape of the lens is segmented, and each segment uses different function curve. The ray tracing principle is used to simulate the transmission performance of X-rays through the polycapillary focusing X-ray lens. And the simulation results were compared with the experimental results.